Poor survival and prediction of prolonged isolated thrombocytopenia post umbilical cord blood transplantation in patients with hematological malignancies. Issue 1 (24th October 2021) - Wu, Yue; Zhang, Zhidan; Tu, Meijuan; Pan, Tianzhong; Ding, Peng; Tang, Baolin; Wan, Xiang; Yao, Wen; Song, Kaidi; Sun, Guangyu; Geng, Liangquan; Qiang, Ping; et al.
Abstract: Prolonged isolated thrombocytopenia (PIT) is a common complication after umbilical cord blood transplantation (UCBT). However, data on PIT prediction and impacts on transplantation outcomes for UCBT patients are rare. We retrospectively analyzed 244 patients with hematological malignancies who received single‐unit UCBT at the First Affiliated Hospital of USTC between August 2018 and December 2019. Among them, PIT occurred in 49 recipients, with a crude incidence of 20.1%. In the PIT patients, the 2‐year cumulative incidence of transplant‐related mortality (TRM) was significantly higher, and the probabilities of 2‐year overall survival, leukemia‐free survival and graft‐versus‐host disease (GVHD)‐free relapse‐free survival were significantly poorer (57.1% vs. 88.6%; 53.1% vs. 81.9%; 22.4% vs. 59.8%; p  < 0.001), without remarkable increases in the cumulative incidence of relapse or chronic GVHD. Importantly, the multivariate analysis revealed that lower high‐resolution HLA compatibility (≤6/10), lower infused CD34 + cell count (≤1.78 × 10 5 /kg), grade II–IV acute GVHD preplatelet engraftment, a lower pretransplantation platelet count (≤100 × 10 9 /L), and a longer neutrophil engraftment time (≥17 days) were independent risk factors for PIT after UCBT. These results demonstrate that PIT is common after UCBT, predicting inferior survival and the need for more monitoring during the early phase.